2020
DOI: 10.3390/membranes10060133
|View full text |Cite
|
Sign up to set email alerts
|

Microfiltration Membranes Modified with Silver Oxide by Plasma Treatment

Abstract: Microfiltration (MF) membranes have been widely used for the separation and concentration of various components in food processing, biotechnology and wastewater treatment. The deposition of components from the feed solution and accumulation of bacteria on the surface and in the membrane matrix greatly reduce the effectiveness of MF. This is due to a decrease in the separation efficiency of the membrane, which contributes to a significant increase in operating costs and the cost of exploitative parts. In recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…For each TiO2 + AgO modified membranes the antibacterial activity of the membrane amounted to 100% compared to the no-coated membrane. These results were similar to those obtained in the previous study, where the AgO coated membranes with different power of magnetron source caused total growth inhibition of E. coli and B. subtilis [11]. The results of reduction (%) in CFU counts are presented in Figure 6.…”
Section: Antibacterial Propertiessupporting
confidence: 90%
See 3 more Smart Citations
“…For each TiO2 + AgO modified membranes the antibacterial activity of the membrane amounted to 100% compared to the no-coated membrane. These results were similar to those obtained in the previous study, where the AgO coated membranes with different power of magnetron source caused total growth inhibition of E. coli and B. subtilis [11]. The results of reduction (%) in CFU counts are presented in Figure 6.…”
Section: Antibacterial Propertiessupporting
confidence: 90%
“…The size of these particles was smaller than 100 nm for magnetron power P M-Ti = 1000 W. Research has shown that the magnetron power has effects on the percentage content for individual metallic elemental composition. The presence of AgO nanoparticles was related to the island nature of the AgO coating grown on a polymer substrate [11]. The antibacterial properties of TiO 2 + AgO coatings were determined for the two following bacteria: Escherichia coli and Bacillus subtilis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is carried out by imparting hydrophilicity, roughness, and other characteristics to the membrane surface [ 3 ]. Membrane modifications can be performed by various methods including surface coating [ 12 ], blending, which introduces bulk modification [ 13 ], combining surface modification with blending [ 14 ], chemical treatment [ 15 ], interfacial polymerization [ 16 ], graft copolymerization [ 17 ], and incorporation of inorganic metal oxides additives such as titania [ 18 ], alumina [ 19 ], zirconia [ 20 ], and silica [ 21 ] in addition to nanoparticles, carbon nanotubes [ 22 ], graphene oxide [ 23 ], and immobilization of antimicrobial additives such as silver nanoparticles [ 24 ] occur during membrane fabrication.…”
Section: Introductionmentioning
confidence: 99%